Corporate real estate in Malaysia higher learning environment / Mohd Fauzee Musa and Zarita Ahmad @ Baharum - Ahmad @ Baharum, Zarita; Musa, Mohd Fauzee (Faculty of Architecture, Planning and Surveying, 2012)
Corporate Real Estate (CRE) is regarded as a part of strategic management in the organization. It is attempted to create awareness and highlight the important of implementing CRE in the educational institution. Educational institution is now facing a challenging task of producing quality human capital and providing students with condusive environment that will enhance their learning, becoming more creative and match the service delivery. Thus, to achive all this any educational institution has to adopt strategy that will help them to add values and enhance their competitiveness. This research is to investigate the components of CRE that create added value to the core business.